Multiple Brain Abscesses in an Immunocompetent Patient With Factor V Leiden Mutation - Saeed Zubair Zafar MD; Najwa Pervin MD; Sukesh Manthri MD; Mukul Bhattarai MD (SAGE Publishing, 2016)
Multiple brain abscesses in an immunocompetent patient is a challenging clinical problem in the medical world despite advances in imaging techniques, laboratory diagnostics, surgical interventions, and antimicrobial treatment. It is a clinical entity that typically tends to occur in the presence of known predisposing factors. Clinicians seek to determine the potential risk factors responsible for the development of brain abscess because it is very crucial for management of this life-threatening condition. At times, like in our case, there are clinical situations where it is difficult to reveal any traditional risk factors. We report a case of multiple brain abscesses in a 51-year-old female with a past medical history significant only for factor V Leiden mutation, and deep vein thrombosis on chronic anticoagulation. She underwent thorough evaluation but no predisposing factors were found. Based on our extensive literature review, this is the index case of multiple brain abscesses in a patient with history of factor V Leiden mutation and the absence of any conventional risk factors. We also postulate a possible mechanism of infection in such patients.